Dietary patterns associated with meeting the WHO free sugars intake guidelines. Issue 9 (8th June 2020) - Steele, Courtney; Eyles, Helen; Te Morenga, Lisa; Ni Mhurchu, Cliona; Cleghorn, Christine
Abstract: Objective: Emerging evidence suggests that free sugars intake in many countries exceeds that recommended by the WHO. However, information regarding real-world dietary patterns associated with meeting the WHO free sugars guidelines is lacking. The current study aimed to determine dietary patterns associated with meeting the guidelines to inform effective free sugars reduction interventions in New Zealand (NZ) and similar high-income countries. Design: Dietary patterns were derived using principal component analysis on repeat 24-h NZ Adult Nutrition Survey dietary recall data. Associations between dietary patterns and the WHO guidelines (<5 and <10 % total energy intake) were determined using logistic regression analyses. Setting: New Zealand. Participants: NZ adults ( n 4721) over 15 years old. Results: Eight dietary patterns were identified: 'takeaway foods and alcohol' was associated with meeting both WHO guidelines; 'contemporary' was associated with meeting the <10 % guideline (males only); 'fast foods, sugar-sweetened beverages and dessert', 'traditional' and 'breakfast foods' were negatively associated with meeting both guidelines; 'sandwich' and 'snack foods' were negatively associated with the <5 % guideline; and 'saturated fats and sugar' was negatively associated with the <10 % guideline. Conclusions: The majority of NZ dietary patterns were not consistent with WHO free sugars guidelines. It is possible to meet the WHO guidelines while consuming a healthier ('contemporary') or energy-dense, nutrient-poor ('takeaway foods and alcohol') diet. However, the majority of energy-dense patterns were not associated with meeting the guidelines. Future nutrition interventions would benefit from focusing on establishing healthier overall diets and reducing consumption and free sugars content of key foods.